Sosialisasi Penggunaan Kantong Belanja Ramah Lingkungan (Reusable) untuk Meminimalisir Sampah Plastik pada Ibu-Ibu TP-PKK di Kelurahan Bugel Kota Tangerang - Humairoh, Humairoh; Atik Atikah; Septian Cahyo Bintoro (Yayasan Literasi Sains Indonesia, 2024)
Community Service Program in the form of educational activities to minimize plastic waste by using environmentally friendly shopping bags among TP-PKK mothers to create an environment free from the use of plastic shopping bags in Bugel Village, Karawaci District, Tangerang City. This needs to be considered more seriously because using plastic bags excessively can create waste that is difficult to decompose on its own, therefore education is intended to invite the Bugel Village community, especially TP-PKK mothers, to reduce plastic bags as shopping containers. The method used is to hold socialization and education activities at a seminar on the impact of waste on the environment for TP-PKK mothers in Bugel Village, Tangerang District, Tangerang City. This socialization was held on Sunday, August 16, 2024 at the NU Branch Hall, Bugel Village, Tangerang District, Tangerang City. By organizing educational programs and awareness campaigns about the use of reusable environmentally friendly shopping bags, we can empower the Bugel Village community to take more sustainable actions, and this initiative will not only help reduce plastic waste but will also improve environmental quality and public health. Through education and active participation, TP-PKK mothers in Bugel Village can build a cleaner community that cares more about the environment, because this effort requires support and active participation from the entire Bugel Village community.